Key elements and theoretical logic of live streaming e-commerce marketing discourse: An analysis based on grounded theory - Haiyan Miao; Yongsheng Yin; Yuanyuan Zhao; Qian Gao (PLoS ONE, 2025)
With the widespread adoption of mobile networks, live streaming e-commerce has experienced robust growth. Marketing discourse plays a crucial role in communication between live streamers and consumers. This study, adhering to the principles of typicality and diversity, selects 37 live streaming e-commerce videos and employs grounded theory for analysis. It explores the key elements of live streaming e-commerce marketing discourse and constructs a theoretical logic model. The study finds that product image portrayal, emphasis on service assurance, customer interaction, and live stream operation are key elements of this marketing discourse. Among them, product image portrayal is central, with its effectiveness dependent on the other three elements. Customer interaction enhances the “presence” of consumers, establishing a “reinforced quasi-social relationship” between streamers and consumers. Emphasizing service assurance effectively reduces consumers’ perceived risk. Live stream operation integrates these three elements to manage the live streaming process and consumers effectively. Based on these elements and the theoretical logic, the design of live streaming e-commerce marketing discourse can be more organized and effective, thereby positively influencing consumers and standardizing live streaming e-commerce activities.